Complications of electrotherapy – the dark side of treatment with cardiac implantable electronic devices - Domagała, Szymon; Domagała, Michał; Chyła, Jakub; Wojciechowska, Celina; Janion, Marianna; Polewczyk, Anna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2018)
In the past years we have been observing the dynamic development of electrotherapy, as evidenced by the steadily rising number of implanted pacemakers (PM), as well as devices used in the treatment of dangerous arrhythmia and heart failure, such as implantable cardioverter defibrillators (ICD) and cardiac resynchronisation therapy (CRT-P/D). This is a consequence of the ageing of the populations of the majority of developed countries and also the gradually widening indications for the use of such devices. Along with the observed rise in the number of new implantations, the number of complications of electrotherapy is rising as well. In view of the increase in the incidence of complications, it is necessary to systematize the knowledge on this subject, because there is still no official classification of this type of complication and guidelines for dealing with such cases do not appear to cover the scale of the problem. In addition, late complications of electrotherapy play the most important role, in which case the removal of the entire pacing system, transvenous lead extraction (TLE), is a challenge due to the older age of leads strongly attached to the venous walls and endocardium of the heart cavity. The present paper presents a modern classification of electrotherapy complications and discusses the types of complications according to the most recent literature reports. Moreover, the diagnosis and management of particular types of complications with the assessment of indications for TLE are discussed.